2018
DOI: 10.1155/2018/7878050
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Dysfunction Provoked by Mercury Chloride Exposure: Evaluation of Cognitive Impairment, Oxidative Stress, Tissue Injury and Nature of Cell Death

Abstract: Mercury (Hg) is a highly toxic metal, which can be found in its inorganic form in the environment. This form presents lower liposolubility and lower absorption in the body. In order to elucidate the possible toxicity of inorganic Hg in the hippocampus, we investigated the potential of low doses of mercury chloride (HgCl2) to promote hippocampal dysfunction by employing a chronic exposure model. For this, 56 rats were exposed to HgCl2 (0.375 mg/kg/day) via the oral route for 45 days. After the exposure period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…It was found that different concentrations of BPA did not affect the body weight of offspring, nor did they significantly regulate the weight of cerebellum, left hippocampus, right hippocampus, spleen, thyroid and pancreas of offspring. It has been reported that toxic exposure patterns can lead to cytotoxicity and cell apoptosis, affecting astrocytes and neurons in the hippocampus, but not necessarily affecting the weight of rats 22 , which is similar to our research. In vivo neuroelectrophysiological experiments showed that the increase of f-EPSP slope and PS amplitude in hippocampal CA1 region of male rats in BPA group was lower than that in control group after high frequency stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…It was found that different concentrations of BPA did not affect the body weight of offspring, nor did they significantly regulate the weight of cerebellum, left hippocampus, right hippocampus, spleen, thyroid and pancreas of offspring. It has been reported that toxic exposure patterns can lead to cytotoxicity and cell apoptosis, affecting astrocytes and neurons in the hippocampus, but not necessarily affecting the weight of rats 22 , which is similar to our research. In vivo neuroelectrophysiological experiments showed that the increase of f-EPSP slope and PS amplitude in hippocampal CA1 region of male rats in BPA group was lower than that in control group after high frequency stimulation.…”
Section: Discussionsupporting
confidence: 91%
“… Aragão et al (2018) demonstrated cognitive impairment and hippocampal damage in rats with oral chronic administration of HgCl 2 . They also found that mercury levels in the hippocampus increased to 0.04 μg/g while the control group had Hg concentrations less than 0.01 μg/g ( Aragão et al, 2018 ). Another study indicated methylmercury chloride induced CNS injury in rats receiving different doses of 0.05, 0.5, and 5 mg/kg Hg against normal saline group.…”
Section: Toxic Effects Of Heavy Metalsmentioning
confidence: 95%
“…Altered hippocampal structure and function induced by MeHg intoxication has been extensively reported (Falluel-Morel et al, 2012;Wu et al, 2016;Aragão et al, 2018). For example, a significant reduction in the total hippocampal DNA content has been found in the neonatal rat, 24 h after a single subcutaneous injection of MeHg (5 µg/g) on the postnatal day 7 (Falluel-Morel et al, 2007).…”
Section: Methylmercury Targets Brain Neurogenesis? Possible Implicatimentioning
confidence: 96%